Enhancing Core Value “AKHLAK” Training Strategy in State-Owned Enterprises within the Oil and Gas Sector - Sari, Novita; Elmi, Farida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose –This research aims to evaluate and enhance the effectiveness of the implementation of AKHLAK values as the cultural foundation in the State-Owned Enterprises (SOE) Oil and Gas Sector. Methodology/approach – This research employs a qualitative triangulation approach. Observations, interviews, and data triangulation are conducted to delve into the impact of the implementation of organizational culture and AKHLAK training in the state-owned enterprise (SOE) Oil and Gas Sector. The research utilizes NVivo12 to support data analysis. Findings – Research findings the need for improvement and collaboration within the business unit. The development of AKHLAK training is recommended through needs analysis, program design, inter-departmental collaboration, continuous learning, emphasis on corporate culture, evaluation and feedback, as well as recognition and acknowledgment. The strategy involves exemplary leadership behavior, clear policies, a collaborative culture, performance evaluation related to AKHLAK, commitment to sustainability, and transparency. Despite positive progress, sustained efforts are required to ensure that AKHLAK values are reflected in employee behavior and support the achievement of corporate goals. Novelty/value – This research contributes by offering profound insights into the implementation of AKHLAK values in the context of State-Owned Enterprises (SOE) in the Oil and Gas Sector. The diversity of findings highlights key aspects that require attention in the development of organizational culture.